Crystal structure and Hirshfeld surface analysis of N-(4-nitrophenyl)-2-(piperidin-1-yl)acetamide (lidocaine analogue) - Imane Maimoune; Benson M. Kariuki; Abderrazzak El Moutaouakil Ala Allah; Intissar Nchioua; Abdulsalam Alsubari; Joel T. Mague; Abdelkader Zarrouk; Youssef Ramli (Acta Crystallographica Section E: Crystallographic Communications)
In the title molecule, C13H17N3O3, the substituents on the phenyl ring are rotated slightly out of the mean plane of the ring but the piperidine moiety is nearly perpendicular to that plane. In the crystal, C—H...O hydrogen bonds form chains of molecules extending along the c-axis direction, which are linked by C=O...π(ring) interactions. A Hirshfeld surface analysis showed the majority of intermolecular interactions to be H...H contacts while O...H/H...O contacts are the second most numerous.